Genomic and Biocontrol Potential of the Crude Lipopeptide by Streptomyces bikiniensis HD-087 Against Magnaporthe oryzae - Liu, Wei; Wang, Jiawen; Li, Shan; Zhang, Huaqian; Meng, Li; Liu, Liping; Ping, Wenxiang; Du, Chunmei (Frontiers in Microbiology, 2022)
Rice blast caused by Magnaporthe oryzae is one of the most destructive plant diseases. The secondary metabolites of Streptomyces have potential as biological control agents against M. oryzae. However, no commercial secondary antimicrobial products of Streptomyces have been found by gene prediction, and, particularly relevant for this study, a biocontrol agent obtained from Streptomyces bikiniensis has yet to be found. In this research, genomic analysis was used to predict the secondary metabolites of Streptomyces, and the ability to develop biocontrol pharmaceuticals rapidly was demonstrated. The complete genome of the S. bikiniensis HD-087 strain was sequenced and revealed a number of key functional gene clusters that contribute to the biosynthesis of active secondary metabolites. The crude extract of lipopeptides (CEL) predicted by NRPS gene clusters was extracted from the fermentation liquid of S. bikiniensis HD-087 by acid precipitation followed by methanol extraction, and surfactins, iturins and fengycins were identified by liquid chromatography-mass spectrometry (LC-MS). In vitro, the CEL of this strain inhibited spore germination and appressorial formation of M. oryzae by destroying membrane integrity and through the leakage of cellular components. In vivo, this CEL reduced the disease index of rice blast by approximately 76.9% on detached leaves, whereas its control effect on leaf blast during pot experiments was approximately 60%. Thus, the S. bikiniensis CEL appears to be a highly suitable alternative to synthetic chemical fungicides for controlling M. oryzae.